A systematic review of the first year of publications on ChatGPT and language education: Examining research on ChatGPT’s use in language learning and teaching - Belle Li; Victoria L. Lowell; Chaoran Wang; Xiangning Li (Computers and Education: Artificial Intelligence)
This systematic review aims to explore published research on the use of ChatGPT in language learning between November 2022 and November 2023, outlining the types of papers, methodologies adopted, publishing journals, major research trends, topics of interest, and existing gaps demanding attention. The PRISMA framework was utilized to capture the latest published articles, selecting 36 articles that met the inclusion criteria. Findings extracted from this review include (1) authors worldwide contribute to this topic, with Asia and North America leading; (2) the wide distribution across various journals underscores the interdisciplinary nature of this research topic, such as computer science, psychology, linguistics, education, and other social sciences; (3) empirical research dominates the literature that is published, with the majority focusing on higher education and ethical considerations. Other findings include that ChatGPT plays multifaceted roles, supporting self-directed language learning, content generation, and teacher workflows. Research gaps include the need for diversified scopes, longitudinal studies, exploration of stakeholders’ perceptions, and assessments of feedback quality.